Expanding the identification of key resource combinations for mid- to long-term growth in electric vehicle market entry - Min-je Cho; Kukjin Bae; Jeongeun Byun; Juneseuk Shin (PLoS ONE, 2025)
This study examines the key resource combinations influencing electric vehicle (EV) adoption, differentiating between short-term market entry and mid- to long-term growth, using the Technology-Organization-Environment (TOE) framework and the Resource-Based View (RBV). Analyzing 12 companies from 2012 to 2022, we find that firms with a well-balanced combination of technological capabilities, organizational strategies, and environmental adaptability achieve sustained market diffusion. A deficiency in any one of these areas hinders long-term success, and excellence in a single resource alone is insufficient. Moreover, the resource requirements for initial market entry differ from those needed for sustained growth, highlighting the need for firms to dynamically adjust their resource strategies based on evolving technological advancements, organizational capabilities, and regulatory and market conditions. Theoretically, this study integrates innovation diffusion theory, RBV, and TOE to offer a comprehensive perspective on EV market dynamics. From a managerial standpoint, companies must develop technological advancements, organizational capabilities, and environmental adaptability to ensure long-term success. Policy-wise, governments can accelerate EV adoption by implementing targeted infrastructure investments, standardizing digital and charging networks, and supporting sustainable innovation through incentives and regulatory frameworks.